PENGARUH CAPITAL INTENSITY, INVENTORY INTENSITY, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Sulistiawati, Ade; Sadewa, Prima (Jurnal Nusa Akuntansi, 2024)
This research aims to determine and provide empirical evidence of the influence of capital intensity, inventory intensity, sales growth and company size on tax avoidance. The type of research used in this research is quantitative. The population used in this research is non-cyclical industrial sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The sample selection technique used purposive sampling technique and obtained 24 companies over 5 years with a total sample data obtained of 120 sample data. Data processing uses Microsoft Office Excel and the Eviews 12 program, by conducting panel data regression model analysis. The results of this research show that capital intensity has no effect on tax avoidance, inventory intensity has no effect on tax avoidance, sales growth has no effect on tax avoidance, company size has an effect on tax avoidance, and simultaneously capital intensity, inventory intensity, sales growth and company size influence on tax avoidance.